1994
DOI: 10.1007/bf02020162
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonographic features of recurrent parotitis in childhood

Abstract: Six children with recurrent parotitis were studied by ultrasound. Of the 12 parotid glands thus observed, 5 were swollen and 7 were not enlarged. Multiple round hypoechoic areas measuring 2-4 mm in diameter were seen in all 5 enlarged parotid glands and in 5 non-enlarged glands. These small hypoechoic areas were larger than the punctate pools of contrast medium shown by sialography. We consider that these hypoechoic areas represented both peripheral sialectasis and surrounding lymphocytic infiltration. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
6

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 8 publications
0
30
0
6
Order By: Relevance
“…At US, chronic and sometimes acute sialadenitis in children (Fig 13), as well as acalculous submandibular gland sialadenitis in adults, have also been described as showing multiple small, round or oval, hypoechoic areas or lesions distributed throughout glandular parenchyma (23,25,31). The differential diagnosis in such cases includes sarcoidosis and other granulomatous diseases, …”
Section: Chronic Sialadenitismentioning
confidence: 99%
“…At US, chronic and sometimes acute sialadenitis in children (Fig 13), as well as acalculous submandibular gland sialadenitis in adults, have also been described as showing multiple small, round or oval, hypoechoic areas or lesions distributed throughout glandular parenchyma (23,25,31). The differential diagnosis in such cases includes sarcoidosis and other granulomatous diseases, …”
Section: Chronic Sialadenitismentioning
confidence: 99%
“…1 Studies have suggested that hypoechoic areas and anechoic areas in parotid are consistent with ductal ectasia and lymph node enlargement. 16 Clinical examination and sonography as a combination are sensitive tools for diagnosis of CRP. MRI Sialography is recently been advocated as useful supplement to conventional sialography.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,7 Chronic recurrent parotitis Chronic recurrent parotitis (CRP) is a rare inflammatory disease of unknown aetiology. 3,8,9 CRP is characterized by multiple episodes of unilateral or bilateral parotid swelling with or without pain. The age of onset usually ranges between 2 years and 7 years.…”
Section: Hiv Sialopathymentioning
confidence: 99%
“…Ultrasound demonstrates multiple minute (1 mm-3 mm) hypoechoic or anechoic focal lesions corresponding to punctate sialectasis on sialography ( Figure 3). 8,9 The imaging differential diagnosis of CRP includes benign lymphoepithelial cysts and juvenile Sjö gren syndrome.…”
Section: Hiv Sialopathymentioning
confidence: 99%